2013
DOI: 10.1002/cphc.201300817
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐Transfer Reactions of Acridine in Water‐Containing Ionic‐Liquid‐Rich Mixtures

Abstract: To assess the potential of ionic liquids (ILs) as a solubilizing media that facilitates proton-transfer reactions, acridine prototropism is investigated using UV/Vis molecular absorbance as well as steady-state and time-resolved fluorescence with different ILs in the presence of a small amount of dilute acid or base. It is found that protonation and deprotonation of acridine, when dissolved in different ILs, can be triggered by the addition of a small amount of dilute aqueous HCl and NaOH, respectively, in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Fig. 36,37 Fluorescence decays for the dye in the presence of DNA, HPbCD and a DNA-HPbCD mixture at pH 4 and 8.5 are displayed in Fig. Present results thus clearly indicate that at pH 8.5 the Ac form of the dye preferentially binds to the HPbCD host, possibly through the axial incorporation of the dye into the host cavity.…”
Section: Circular Dichroism Measurementsmentioning
confidence: 62%
See 1 more Smart Citation
“…Fig. 36,37 Fluorescence decays for the dye in the presence of DNA, HPbCD and a DNA-HPbCD mixture at pH 4 and 8.5 are displayed in Fig. Present results thus clearly indicate that at pH 8.5 the Ac form of the dye preferentially binds to the HPbCD host, possibly through the axial incorporation of the dye into the host cavity.…”
Section: Circular Dichroism Measurementsmentioning
confidence: 62%
“…Scheme 1), with a pK a of 5.4. [36][37][38] Taking advantage of the strikingly different binding behaviour of the HPbCD macrocycle towards the protonated and neutral forms of acridine dye, as observed in the present study, we have demonstrated an effective pH-triggered controlled and targeted release of the dye from the HPbCD cavity, a potential drug carrier vehicle, to the target site of DNA, which is a major goal in chemotherapeutic applications. 19 Acridine and its derivatives are potent DNA binders because of their planar structures, 29,30,32 and are well-recognized as drugs showing carcinogenic effect due to their property to bind strongly with DNA.…”
Section: Introductionmentioning
confidence: 57%
“…Reasonably, the fluorescence enhancement of this band could be rationalized considering the inhibition of the photoinduced electron transfer effect (PET), due to the protonation of the benzylic nitrogen groups occurring in correspondence of the formation in solution of the tetra and tri‐protonated species of L1 ([H 4 L1] 4+ , [H 3 L1] 3+ )(Figure b). Finally, for acidic conditions (pH ≤ 4) spectra become more structured and red‐shifted of about 20 nm, featuring a band which is diagnostic of the formation of the acridinium cation, thus confirming the protonation of the heteroaromatic nitrogen when the penta‐protonated specie [H 5 L1] 5+ occurs in solution. A somewhat similar behavior was also found in the case of L2 (Figure S8).…”
Section: Resultsmentioning
confidence: 77%
“…The fluorescence decays of both AcH + and Ac are single exponential in nature in the absence of SCX4 with their characteristic lifetime (τ f ) values as 30.3 ns and 7.8 ns, respectively …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, depending upon the pH of the solution, the dye exists in its protonated form (AcH + ) at acidic pH condition and in its neutral form (Ac) at alkaline pH condition . Significant microenvironment sensitive changes in the spectroscopic properties of acridine dyes make them useful fluorescence probes to study local environments of various constrained systems like micelles, reverse micelles, macrocyclic nanocavities, etc . In the present study we have found large changes in the photophysical and acid‐base properties of acridine dye upon its encapsulation into SCX4 host cavity and striking modulations in the properties in the presence of the competitive binder, AcCh, as the stimulus cum analyte of interest following FIDA.…”
Section: Introductionmentioning
confidence: 99%